Efektivitas Penggunaan Al(OH)3 Sebagai Coprecipitant Pada Analisa Besi (Fe2+) - Dela Gustika; Edi Nasra (Departemen Kimia FMIPA UNP, 2022)
The concentration of metals in the water is generally very small, so it is difficult to determine by AAS. For this reason, before measuring with AAS, it is necessary to do pretreatment. One of the pretreatment that are commonly used to determine metal concentrations at low concentrations is coprecipitation, where this method is one of the pre-concentration methods. Preconcentration is a concentration technique used when the available sample has a very low concentration. There are several methods of preconcentration, one of which is the coprecipitation method. In this study, the coprecipitation method was used to analyze the metal content of Fe2+ in very small concentrations which would later be measured using an atomic absorption spectrophotometer. The purpose of this study was to determine the optimum conditions of coprecipitation of Fe2+ metal ions using Al(OH)3 as coprecipitant. The result obtained in this study were, the optimum conditions for Fe2+ metal ion coprecipitations occured at pH 9, Al3+ concentration 0,2 M, and the long deposition time occurred at 15 hours.